Bee fauna of Slovenia: checklist of species (Hymenoptera: Apoidea) - Gogala, Andrej (Scopolia, 1999)
Listed in the present article are 536 bee species known to live in Slovenia, according to the published records, their presence in collections preserved in the Slovenian Museum of Natural History, or such as found by the author in recent surveys. The distribution of the species in Slovenia are shown according to the phytogeographical regions. Data on the biology of species include foodplant preferences, nesting habits or cleptoparastic way of life.
Keywords: Apoidea; zoologija; zoology; Slovenia; Slovenija; čebele; favna; entomologija